Dichotomy of the human T cell response to Leishmania antigens. I. Th1-like response to Leishmania major promastigote antigens in individuals recovered from cutaneous leishmaniasis. - Kemp, M (1994)
The T cell response to antigens from Leishmania major promastigotes was investigated in peripheral blood mononuclear cells from Sudanese individuals with a history of cutaneous leishmaniasis (CL), Sudanese individuals with positive DTH reaction in the leishmanin skin test but with no history of skin lesions, and in Danes without known exposure to Leishmania parasites. Proliferation and production of interferon-gamma (IFN-gamma) and IL-4 in antigen-stimulated cultures was measured. Lymphocytes from individuals with a history of CL proliferated vigorously and produced IFN-gamma after stimulation with either a crude preparation of L. major antigens or the major surface protease gp63. These cultures produced no or only little IL-4. Also cells from leishmanin skin test-positive donors with no history of CL produced IFN-gamma and no IL-4 in response to L. major antigens. Cells from the unexposed Danes were not activated by gp63. The cells from Danish donors produced either IFN-gamma or IL-4, but not both cytokines after incubation with the crude preparation of L. major antigens. The data show that the T cell response to Leishmania antigens in humans who have had uncomplicated CL or subclinical L. major infection is an IFN-gamma-producing Th1-like response.